2021
DOI: 10.1002/smll.202102841
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Engineering of Laser‐Induced Graphene for Potential‐Driven Broad‐Spectrum Antimicrobial and Antiviral Applications

Abstract: Worldwide, countless deaths have been caused by the coronavirus disease 2019. In addition to the virus variants, an increasing number of fatal fungal infections have been reported, which further exacerbates the scenario. Therefore, the development of porous surfaces with both antiviral and antimicrobial capacities is of urgent need. Here, a cost‐effective, nontoxic, and metal‐free strategy is reported for the surface engineering of laser‐induced graphene (LIG). The authors covalently engineer the surface poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 71 publications
1
13
0
Order By: Relevance
“…7 e vividly shows the schematic diagram of morphology transformation of HCoV-OC43. These results suggest that SNF-Cu 2-x S have an excellent antiviral activity that is close to the literature [48] , [54] , [55] .…”
Section: Resultssupporting
confidence: 90%
“…7 e vividly shows the schematic diagram of morphology transformation of HCoV-OC43. These results suggest that SNF-Cu 2-x S have an excellent antiviral activity that is close to the literature [48] , [54] , [55] .…”
Section: Resultssupporting
confidence: 90%
“…reported that molecular engineered graphene can be used for broad spectrum antiviral applications. [ 25 ]…”
Section: The Antiviral Action Of Nanomaterials Against Corona Virus M...mentioning
confidence: 99%
“…At the same time, graphene itself is able to show moderate antibacterial activity in the absence of light and shows stronger bacterial inactivation in the presence of light due to the photothermal effect. 27 , 28 Moreover, the application of photocatalytic nanoparticles as a powder will also be difficult to recycle and cause secondary pollution problems. 29 , 30 So far, there are relatively few reports about the combination of the excellent filtration ability of glass microfiber and the rapid antibacterial ability of zinc oxide/graphene photocatalytic composite particles in the synthesis of multifunctional air filters.…”
Section: Introductionmentioning
confidence: 99%
“…Graphene has also become a new functional material for antibacterial applications due to its unique characteristics, such as high electrical conductivity, excellent solubility, biocompatibility, and relatively low cytotoxicity to mammalian cells, which could provide more active sites for ZnO nanoparticles in order to improve the photocatalytic antibacterial efficiency by effectively separating photo-generated electrons and holes. At the same time, graphene itself is able to show moderate antibacterial activity in the absence of light and shows stronger bacterial inactivation in the presence of light due to the photothermal effect. , Moreover, the application of photocatalytic nanoparticles as a powder will also be difficult to recycle and cause secondary pollution problems. , So far, there are relatively few reports about the combination of the excellent filtration ability of glass microfiber and the rapid antibacterial ability of zinc oxide/graphene photocatalytic composite particles in the synthesis of multifunctional air filters. When glass fibers are used for air filtration materials, the finer the diameter of the fibers, the better the air filtration effect. , However, too fine a fiber will lead to a reduction in its strength, and thus, it is prone to breakage and damage, and the fiber will instead become a contaminant like the impurities originally planned to be filtered out.…”
Section: Introductionmentioning
confidence: 99%